The Academic Language Development Program: A Capacity-building Approach to Supporting Secondary Teachers of English Learners - Susan O'Hara; Robert Pritchard; Jeff Zwiers (Adult Education Research Conference, 2014)
This study reports the results of the first phase of a multiyear project designed to develop a capacity-building, professional development model for teachers of English learners. Preliminary analyses show that teacher knowledge and use of appropriate instructional approaches improved, but challenges that still need to be addressed were identified.